Computational biology exposed a common pathogenic mechanism in influenza A and Guillain-Barré syndrome - Ye Deng; Zhongwen Tang; Qiong Chen; Xujuan Hu; Yingjie Zhang; Meng Chen; Qiongya Wang; Fuli Ren (PLoS ONE, 2026)
Influenza virus A (H1N1) can lead to acute respiratory infection, while Guillain-Barré Syndrome (GBS) is an autoimmune peripheral neuropathy, which can work as a post-infectious disease. There are clinical observations showing the existence of a possible relationship between the presence of H1N1 infection and GBS disease, and therefore there could be common immunopathological pathways associated with H1N1 infection and GBS. The possible similarity between H1N1 infection and GBS was further investigated using integrated bioinformatics and systems biology approaches. Differentially expressed genes (DEGs) were identified from GEO datasets related to H1N1 infection and GBS. Enrichment analysis was conducted to understand the functional roles of identified DEGs by performing GO and KEGG pathway analysis. For the interacting proteins of the common DEGs, protein-protein interaction (PPI) network analysis helped to find out TLR4, TNF, and ITGAM as key hub genes. These hub genes might have common molecular pathways in H1N1 infection and GBS. To predict possible drug targets for treatment, analysis of interactions between hub genes and miRNAs, TFs, and related diseases was performed.